Pengaruh Penggunaan Video Pembelajaran Berorientasi HOTS terhadap Motivasi dan Hasil Belajar Materi Gaya Siswa SD Negeri Dlisen 02 - Indalipah Indalipah; Joko Siswanto; Fenny Roshayanti (Perkumpulan Kualitama Edukatika Indonesia, 2022)
The background that drives this research is the low motivation to learn and student learning outcomes. This is due to the lack of teacher knowledge about varied learning models and the use of media that is less than optimal for students. The problems in this study are (1) How is the Effect of Using HOTS Oriented Learning Videos on Learning Motivation for Style Materials at SD Negeri Dlisen 02?; (2) How is the Effect of Using HOTS Oriented Learning Videos on Learning Outcomes of Student Style Materials at SD Negeri Dlisen 02?. This type of research is experimental. Hypothesis test of students' learning motivation there is a difference in motivation between classes that receive learning with video and classes that do not use video. This is evidenced from the results of the t-test of pretest learning outcomes concluded that there is a significant difference in Science learning outcomes in style material. Testing the hypothesis of student learning outcomes there is a difference in learning outcomes between classes that receive learning with video and classes that do not use video. From the results of the t-test of pretest learning outcomes in the class, the significance value obtained by the t-test. It can be concluded that there is a significant difference in Science learning outcomes in style material in class students. The variance test of learning motivation has an effect on the use of hots-oriented learning videos on learning motivation at SD Negeri Dlisen 02. The significance value is Sig (2-tailed) 0.001 (0.001 < 0.05), with a perfect relationship degree of 0.879 which is included in the Pearson correlation range of 0.81 up to 1.00 so that it can be concluded that there is an effect of the application of HOTS-oriented learning videos on science learning motivation on style material for fourth grade students. The variance test of learning outcomes has the effect of using hots-oriented learning videos on learning outcomes at SD Negeri Dlisen 02. The significance value is Sig (2-tailed) 0.001 (0.001 < 0.05), with a perfect relationship degree of 0.824 which is included in the Pearson correlation range of 0.81 up to 1.00 so it can be concluded that there is an effect of the application of HOTS-oriented learning videos on science learning outcomes on style material for fourth grade students.